Жанубий қорақалпоғистондаги баъзи ойконимларнинг лексик-семантик таснифи хусусида - Холмуратов, И (SCIENCE and SOCIETY, 2021)
Historically, from socio-political and cultural-educational, nationality and economical points of view names, partly, oikonyms are of special importance. For they represent national, cultural-educational potential and view of nations, their love, respect and honour to the nature and society.
Keywords: topobase; oikonyms; ethno oikonyms; indicator; street; auls; mahallas; village; city